Peran Istri Nelayan dalam Meningkatkan Perekonomian Keluarga di Desa Batu Nampar Selatan Kecamatan Jerowaru - Gapari, Muhamad Zaril (Lembaga Yasin AlSys, 2021)
The sea is a source of livelihood for fishermen's families, and with the richness of the sea that exists in Indonesia, it should make the fishermen's family life better than just fit for life, but in fact the living conditions of fishermen's families who inhabit this coast contribute more to the poverty rate. in Indonesia, whereas the available and abundant marine natural resources can open up opportunities and opportunities in managing resources wisely by paying attention to their sustainability. This form of poverty and ignorance is clearly seen in the lack of facilities and infrastructure for fishery production and the low quality of human resources ( coastal women ) caused by low levels of education so that the ability and skills in managing production activities, mastery of technology and management are also low. The purpose of this study is to determine the economic life of fishermen communities and the role of fishermen's wives in improving the family economy. This type of research is a descriptive type of research with a qualitative approach . This research is located in Batu Nampar Selatan Village, Jerowaru District. Where the population of this study were all fishermen's wives in Batu Nampar Selatan Village as many as 726 and the samples taken were 30 people. The sampling technique was using purposive sampling technique. The data collection technique was carried out by means of observation, interviews and documentation, while the data analysis used qualitative analysis which was inductive in nature. Based on the findings in the field, it can be reported that the life of the fishermen in Batu Nampar Selatan is classified as poor and underdeveloped, because it can be seen from the people who have a low standard of living, lack of education, and are classified as underdeveloped, uncertain income causes fishermen to always be in poverty and deprivation . Furthermore, the role of fishermen's wives in Batu Nampar Selatan Village has a dual role. The factor that encourages fishermen's wives to participate in earning a living is because their husband's income is not sufficient for their family's daily needs, but even though they can generate income for the family, it does not necessarily change their living conditions because the wife's income can only fulfill their daily needs .